Evolution of banking system in India since 1900 - Chawla, O. P. (Om Prakash), 1934- (Sage publication India, 2019)
Evolution of Banking System in India since 1900 presents a detailed analysis of the evolution, growth and development of the Indian banking system in the last 117 years, from 1900 to 2017. The book focuses on major events that have significantly impacted the banking system to change the course of its history. It covers major policy, structural, regulatory and legislative changes that formed the background as well as the springboard of the working of banks, followed by a detailed analysis of the significant financials. It also uncovers the most significant events and developments of scheduled commercial banking, which has evolved from a small unorganized system to a technology-oriented regulated one.